Changes in body weight and health behaviors of overweight children during the COVID-19 pandemic - Bergmann, Gabriel Gustavo (2020)
The aim of this study was to describe the perception of parents of overweight children about the effects of the period of social distancing due to COVID-19 on body weight (BW), level of physical activity (PA), time spent in sedentary behavior (SB) and their children's eating habits and sleep. Parents of 47 overweight children (11.1 ± 1.33 years) were interviewed by telephone. Questions about the perception regarding BW and the four behaviors related to the health of their children during the period of social distancing were asked. The increase in BW was perceived by 61.7% of children and for almost all of them (93.6%) reductions in PA levels were reported, with 72.4% reducing participation in vigorous PA. An increase in time using smartphones, tablets, and microcomputers was observed in 65.9% of children. Favorable changes were noted in relation to quality (34.1%) and daily sleep time (51.1%). Favorable changes in the consumption of fruits (36.2%) and soft drinks (21.2%) and unfavorable changes in the consumption of vegetables (19.1%) and sweets and snacks (26.2%) were also reported. Four and a half months after the start of the social distancing measures due to the COVID-19 pandemic, overweight children increased the BW and changed the levels of PA and SB in an unfavorable way according to their parents. On the other hand, they started sleeping more and with higher quality and consuming more fruits and less soft drinks.